ANALISIS PENTINGNYA EVALUASI PEMBELAJARAN DALAM MENINGKATKAN PEMAHAMAN SISWA SEKOLAH DASAR - Mahayun Sari, Gandes Rahmi; Lisda Pariha; Putri Laura Nugraha; Sofyan Iskandar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning evaluation plays a crucial role in enhancing students' understanding in elementary schools, especially amidst the low understanding of educators regarding evaluation concepts and practices. This research aims to explore the role, implementation, and factors influencing learning evaluation. The methodology used is a literature review, collecting and analyzing relevant written sources. The research results show that evaluation not only serves to measure the effectiveness of learning but also provides constructive feedback for teachers and students. In addition, the research identified various hindering factors, such as the lack of teacher understanding and student motivation. With improvements in the evaluation process, it is hoped that the quality of education can increase and students' understanding of the subject matter can be optimally supported.